(untitled) - Solórzano, Helen S. (White plains, NY, 2009)
This book includes: Ten thematic units to develop academic skills in English while building test-taking confidence; Integrated skill practice to develop critical thinking and communicative competence; Authentic TOEFL® iBT practice sets created by ETS especially for this series; Practical tips to sharpen test-taking strategies; Teacher's Manuals with evaluation tools to track students' progress and actual student responses (Listening and Speaking) at all score levels.
Keywords: Tiếng Anh,English language; Nói tiếng Anh,Spoken English